Psychological Support in a COVID-19 Hospital: A Community Case Study - Rizzi, Damiano; Asperges, Erika; Rovati, Anna; Bigoni, Francesca; Pistillo, Elena; Corsico, Angelo; Mojoli, Francesco; Perlini, Stefano; Bruno, Raffaele (Frontiers in Psychology, 2022)
Burnout is a well-documented entity in Care Workers population, affecting up to 50% of physicians, just as it is equally well established that managing an infectious disease outbreak, such as Covid-19, increases Post-Traumatic Stress Disorder (PTSD) and the psychological burden. Mental health support, in the form of formal or remote sessions, has been shown to be helpful to health care staff, despite the organizational difficulties in an emergency. During the first emergence of Covid-19 in Italy, the Scientific Institute for Research, Hospitalization and Health Care IRCCS Policlinico San Matteo Foundation (Pavia), the Italian hospital that treated "patient 1", has activated an agreement with the Soleterre Foundation, an international Non-Governmental Organization (NGO) that manages health emergency projects, to provide psychological support. A task force of psychologists was created with the aim of designing and administering a Therapeutic Mental Health Assessment for COVID-19 Care Workers (TMHA COVID-19 CWs) to evaluate and support health care workers’ mental health. An assessment battery was developed to evaluate symptoms and behaviors associated with trauma and the corresponding maladaptive behaviors (the National Stressful Events Survey for PTSD-Short Scale “NSESSS” and the Diagnostic and Statistical Manual of Mental Disorders “DSM-5” Self-Rated Level 1 transversal Symptom Measure – Adult). The TMHA COVID-19 CWs was regularly administered by the team of psychologists to healthcare staff in the wards.  107 care workers (44 males, mean age 40±15) across Intensive Care Units (ICUs), the emergency room and medical wards were administered the TMHA COVID-19 CWs. PTSD symptoms were reported as severe by 13% of the population. Depressive symptoms as severe for 7% and Anxiety symptoms as severe for 14%. Severe psychotic symptoms were experienced by 2% and severe suicidal thoughts by 1% of the population. The identification of these symptoms, when moderate or severe, allowed an early intervention through individual session. In fact, 280 individual support sessions were offered. Therefore, we considered our project a protective and support factor for healthcare workers’ mental well-being and we recommend implementing a mental health screening program in wards involved in Covid-19 patients’ care.